Genetic ablation of VIAAT in glycinergic neurons causes a severe respiratory phenotype and perinatal death - Rahman, Jamilur; Besser, Stefanie; Schnell, Christian; Eulenburg, Volker; Hirrlinger, Johannes; Wojcik, Sonja M; Huelsmann, Swen (Brain Structure & Function, 2015)
Both glycinergic and GABAergic neurons require the vesicular inhibitory amino acid transporter (VIAAT) for synaptic vesicle filling. Presynaptic GABA concentrations are determined by the GABA-synthesizing enzymes glutamate decarboxylase (GAD)65 and GAD67, whereas the presynaptic glycine content depends on the plasma membrane glycine transporter 2 (GlyT2). Although severely impaired, glycinergic transmission is not completely absent in GlyT2-knockout mice, suggesting that other routes of glycine uptake or de novo synthesis of glycine exist in presynaptic terminals. To investigate the consequences of a complete loss of glycinergic transmission, we generated a mouse line with a conditional ablation of VIAAT in glycinergic neurons by crossing mice with loxP-flanked VIAAT alleles with a GlyT2-Cre transgenic mouse line. Interestingly, conditional VIAAT knockout (VIAAT cKO) mice were not viable at birth. In addition to the dominant respiratory failure, VIAAT cKO showed an umbilical hernia and a cleft palate. Immunohistochemistry revealed an almost complete depletion of VIAAT in the brainstem. Electrophysiology revealed the absence of both spontaneous glycinergic and GABAergic inhibitory postsynaptic currents from hypoglossal motoneurons. Our results demonstrate that the deletion of VIAAT in GlyT2-Cre expressing neurons also strongly affects GABAergic transmission and suggest a large overlap of the glycinergic and the GABAergic neuron population during early development in the caudal parts of the brai
EVALuna2:4703